Emotional competence profile in secondary school counselors: controversy or need? - Fernández Tilve, María Dolores; Malvar Méndez, María Laura; Varela Tembra, Juan José (Frontiers in Education, 2024)
It is out of doubt that little attention is paid to the emotional competences of secondary school counselors in research activity, as well as in their initial and ongoing training. It seems that emotional well-being is still a pending issue that may even generate some controversy, even though, today, it is defined as a clear strategy in mental health plans. Undoubtedly, we are facing a content that facilitates the contrast of points of view and social commitment as an inherent part of the democratic process. Therefore, it was decided to carry out a study, of enormous relevance, with the purpose of knowing the perceptions of secondary school counselors within the Autonomous Community of Galicia regarding emotional competences for an ideal counseling practice in complex times and moments with great challenges in the field of educational equity. Specifically, an evaluation study was carried out on the level of training received by school counselors in emotional competences and thus be able to have a diagnosis, identifying possible strengths and weaknesses. A study with a quantitative based methodology which uses the questionnaire for data collection as a main research technique. The findings obtained suggest that the quality of the teaching and learning processes in secondary schools would be substantially improved if the emotional competence profile of the counselors was considered. In particular, the interest that emotional competences arouse in counselors is confirmed, at the same time, they recognize that they can help them properly to manage the relationship processes and, the personal balance. This research, one of the first carried out in Galicia on emotional competences in secondary school counselors, provides empirical data of great interest for future training plans that are more in line with social and professional expectations, since it provides an x-ray unique, revealing, valid and real statement of the state of the matter.